LEXICALLY-BASED LANGUAGE TEACHING: METAPHOR FOR ENHANCING LEARNING - Siusana Kweldju (Universitas Katolik Indonesia Atma Jaya, 2005)
Although metaphor has been ignored, lexically-based language teaching considers metaphor as an important aspect to learn. Learning metaphor helps learners improve their general proficiency in SLA because metaphor is a key to human memory organization, so that it enhances the acquisition of vocabulary, improves comprehension, clarifies ideas, extends thought, and increases attention. As long as meaning is the center of second language learning, metaphorical meaning must also be included because metaphor is pervasive in every day language and thought. Raising students’ awareness towards metaphor helps develop their metaphorical competence, which is a requirement for native-like proficiency. The importance of metaphor in lexically-based language teaching lends support from, cognitive linguistics the theory of mental lexicon, cognitive linguistics, second language acquisition, and the abundant use of metaphor in daily use. Keywords: lexically-based language teaching, metaphor